Castleman Disease: Insights from a Case Series and Literature Review - Jerin James; Sanudev Sadanandan Vadakke Puthiyottil; Johan George; Arathi Edayattil; Vivek Mathew James; Swapna Dominic; Supriya N. K. (Indian Journal of Medical and Paediatric Oncology)
Castleman disease (CD), a rare lymphoproliferative disorder with unicentric (UCD) and multicentric (MCD) subtypes, presents significant diagnostic and therapeutic challenges due to its clinical heterogeneity. This case series of four patients highlights rare and diverse clinical presentations of CD, including atypical anatomical sites and paraneoplastic pemphigus. Diagnostic challenges included differentiating CD from malignancies or autoimmune disorders, emphasizing the critical role of histopathology. UCD pathogenesis may involve follicular dendritic cell mutations, whereas MCD subtypes are driven by human herpesvirus (HHV)-8-associated viral interleukin-6 or idiopathic cytokine dysregulation. Treatment strategies varied, with surgery preferred for UCD and immunomodulators (siltuximab, rituximab) for MCD. Challenges such as limited standardized protocols in resource-constrained settings and biomarker variability underscore the need for individualized therapy. Emerging approaches, including cytokine-targeted therapies and bortezomib, show promise for refractory cases. This study reinforces the importance of multidisciplinary collaboration, early histopathological diagnosis, and long-term monitoring to optimize outcomes. By integrating clinical experiences with literature, it advocates for refined diagnostic criteria and context-specific therapeutic algorithms, urging further research to address gaps in managing this complex disease.